China's (Uneven) Progress Against Poverty - Ravallion, Martin (World Bank, Washington, D.C., 2013)
While the incidence of extreme poverty in China fell dramatically over 1980-2001, progress was uneven over time and across provinces. Rural areas accounted for the bulk of the gains to the poor, though migration to urban areas helped. The pattern of growth mattered. Rural economic growth was far more important to national poverty reduction than urban economic growth. Agriculture played a far more important role than the secondary or tertiary sources of gross domestic product (GDP). Rising inequality within the rural sector greatly slowed poverty reduction. Provinces starting with relatively high inequality saw slower progress against poverty, due both to lower growth and a lower growth elasticity of poverty reduction. Taxation of farmers and inflation hurt the poor. External trade had little short-term impact.